Control of winter forage pea diseases by pea-oat intercropping under field conditions - Živanov, Dalibor; Jevtić, Radivoje; Tančić, Sonja; Vasiljević, Sanja; Maširević, Stevan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
A field experiment was conducted at the experimental field of the Institute of Field and Vegetable Crops in Novi Sad to investigate the effect of forage winter pea and winter oat intercropping on ascochyta blight and powdery mildew infections. Seeding rations of pea and oat in Treatment 1 (50:50%) and Treatment 2 (75:25%, respectively) reduced ascochyta leaf infection by 32.5% and 12.8%, and powdery mildew infection by 12.3% and 17.5%, respectively, compared to pea monoculture used as a control (Treatment 3). The same seeding rations in Treatment 1 and 2 reduced ascochyta blight on pea plants by 37.2% and 18.3%, respectively. However, there were no significant differences between the treatments in reducing powdery mildew on plants. The effects of different treatments on the average number of pods per plant, seed per pod, shriveled pods and seed weight were analyzed using Spearman’s correlation coefficient. Negative but not statistically significant effects on those measured parameters were registered in Treatments 2 and 3, while Treatment 1 showed positive effects on all parameters except shriveled pods. According to all data obtained in this research, the intercropping mixture of pea and oat at 50:50% seeding ratio had the best effect on the measured parameters while the intercropping mixture of pea and oat at 75:25% seeding ratio had low to moderate effect in comparison with pea monocrop.